2019
DOI: 10.1016/j.csda.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Covariance-insured screening

Abstract: Modern bio-technologies have produced a vast amount of high-throughput data with the number of predictors far greater than the sample size. In order to identify more novel biomarkers and understand biological mechanisms, it is vital to detect signals weakly associated with outcomes among ultrahigh-dimensional predictors. However, existing screening methods, which typically ignore correlation information, are likely to miss weak signals. By incorporating the inter-feature dependence, a covariance-insured screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…To incorporate the correlation information, He et al () proposed compartmentalizing covariates into blocks so that variables from distinct blocks are less correlated. The algorithm starts from the idea of thresholding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To incorporate the correlation information, He et al () proposed compartmentalizing covariates into blocks so that variables from distinct blocks are less correlated. The algorithm starts from the idea of thresholding.…”
Section: Methodsmentioning
confidence: 99%
“…The success of SIS relies on a fundamental assumption that the true association between the individual predictors and the response can be inferred from their marginal associations. To account for the violation of this assumption, recent researches have expressed a growing interest in conducting multivariate screenings (Cho & Fryzlewicz, ; Cui, Li, & Zhong, ; Hall & Miller, ; He et al, ; Jin, Zhang, & Zhang, ; Kang, Hong, & Li, ; Li, Peng, Zhang, & Zhu, ; Wang & Leng, ; Zhu, Li, Li, & Zhu, ). In particular, according to the reports by the authors, the high‐dimensional ordinary‐least squares projection (HOLP; Wang & Leng, ) substantially improves variable screening accuracy of SIS for many scenarios with theoretical supports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate fine-mapping model requires exact knowledge of the LD pattern among the SNPs within a GWAS locus [4,7,8,13,14]. Generally, the LD pattern refers to two aspects: i) the local aspect, pairwise LD scores between SNPs which are directly available, and ii) the global aspect, the (latent) network topological structure (e.g., the community structure) of the LD matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the LD pattern refers to two aspects: i) the local aspect, pairwise LD scores between SNPs which are directly available, and ii) the global aspect, the (latent) network topological structure (e.g., the community structure) of the LD matrix. A large body of literature on multivariate statistics has shown that the accuracy of variable selection relies on the accurate knowledge of the network structure of the dependence between predictors [14][15][16][17][18][19]. However, the network structure of the LD pattern measured using the commonly used haplotype block methods cannot accurately reveal the latent network structure of the LD pattern.…”
Section: Introductionmentioning
confidence: 99%